Role of Interleukin-17A in the Pathomechanisms of Periodontitis and Related Systemic Chronic Inflammatory Diseases - Feng, Yi; Chen, Zheng; Tu, Shao-Qin; Wei, Jia-Ming; Hou, Yu-Luan; Kuang, Zhi-Li; Kang, Xiao-Ning; Ai, Hong (Frontiers in Immunology, 2022)
Periodontitis is a chronic inflammatory and destructive disease caused by periodontal microbial infection and mediated by host immune response. As the main cause of loosening and loss of teeth in adults, it is considered to be one of the most common and serious oral diseases in the world. The co-existence of periodontitis and systemic chronic inflammatory diseases such as rheumatoid arthritis, psoriasis, inflammatory bowel disease, diabetes and so on is very common. It has been found that interleukin-17A (IL-17A) secreted by various innate and adaptive immune cells can activate a series of inflammatory cascade reactions, which mediates the occurrence and development of periodontitis and related systemic chronic inflammatory diseases. In this work, we review the role of IL-17A in the pathomechanisms of periodontitis and related systemic chronic inflammatory diseases, and briefly discuss the therapeutic potential of cytokine targeted agents that modulate the IL-17A signaling. A deep understanding of the possible molecular mechanisms in the relationship between periodontitis and systemic diseases will help dentists and physicians update their clinical diagnosis and treatment ideas.